ذكر المسافات وصور الأقاليم - Al-Balkhi | البَلْخِي, Ahmed bin Sahl Abu Zaid | أحمد بن سهل أبو زيد (King Abdulaziz Complex for Endowment Libraries | مجمع الملك عبدالعزيز للمكتبات الوقفية, 2023)
His Manuscript Suwar al-Aqtaliya consists mainly of geographical maps. This led him to found the "Balkhi School" of land mapping in Baghdad. The geographers of this school also wrote extensively about the peoples, products, and customs of regions in the Islamic world, with little interest in the non-Muslim worlds. | يتألف مخطوط صور الأقاليم بشكل رئيسي من الخرائط الجغرافية. قاده ذلك إلى تأسيس «مدرسة البلخي» لرسم الخرائط الأرضية في بغداد. كما كتب الجغرافيون في هذه المدرسة عن الشعوب والمنتجات والعادات في المناطق في العالم الإسلامي بتوسع مع القليل من الاهتمام بالعوالم غير المسلمة